Village Government Readiness Toward the Adoption of E-Government - Rini Mayasari; Nono Heryana; Agustia Hananto (Buana Information Technology and Computer Sciences (BIT and CS), 2023)
Public services in the village are very important because the village is the smallest part of the administrative government system in Indonesia and is the front line of public services. Technological developments encourage the government to manage public services to improve the ineffective bureaucratic paradigm. E-government is a solution to improve public services. One of the failures in implementing E-Government is the village government's lack of readiness to adopt information technology. The research method used in this research is descriptive qualitative. The results obtained suggest that the STOPE framework model consisting of Strategy, Technology, Organization, People, and Environment is the most appropriate model to analyze the readiness of the village government. Of the 5 domains that were assessed, 3 domains received the Very Ready predicate and 2 domains received the Ready predicate